2002
DOI: 10.1179/026708302225003604
|View full text |Cite
|
Sign up to set email alerts
|

Bending in aluminium alloys AA 6111 and AA 5754 using the cantilever bend test

Abstract: Bendability is an important forming parameter in many applications, but particularly in automotive parts where the formed parts in structures can be quite complex, and where outer skins are joined to inner panels through the hemming process. In this paper the bend performance of two aluminium based automotive alloys, the heat treatable skin alloy, AA 6111 and the non-heat treatable structural alloy AA 5754, are assessed by the cantilever bend test. This test enables the load ± bend angle relationship to be mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…For materials in which the neutral axis remains at the center of the sheet, such as materials with limited ductility, they derived C = 50, whereas for a moving neutral axis, they suggested C = 60. Previous results [10,12] on bending in Al alloys have shown general agreement with Eq. [5], but with a C value of about 70.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…For materials in which the neutral axis remains at the center of the sheet, such as materials with limited ductility, they derived C = 50, whereas for a moving neutral axis, they suggested C = 60. Previous results [10,12] on bending in Al alloys have shown general agreement with Eq. [5], but with a C value of about 70.…”
Section: Discussionsupporting
confidence: 70%
“…Bending in monolithic Al alloys is still not well understood, but recent publications [10][11][12] have shown that the surface develops severe topographical features both in the matrix, where strain localization in severe bands develops, and at grain boundaries. In addition, cracking is initiated in these regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized bending may also occur as wrinkling, which is a failure mode often seen in sheet forming and in the compressive zone during tube bending where local buckling or bending instability occurs. In many cases, bending occurs in the later forming stages, where the existing residual strains can cause accelerated strain localization and reduce bendability as shown by Sarkar et al (2001) and Lloyd et al (2002). Bending of AA5754 sheet has been performed and simulated using techniques such wrap bending (Hu et al, 2010) and V-bending (Toros et al, 2011), both of which produce inhomogeneous deformation due to the interaction with the loading tool.…”
Section: Introductionmentioning
confidence: 99%
“…Leo et al (2016)reported that, fast cooling rates cause the solute atoms may be trapped in Al matrix without precipitating particles. Bending is an important forming property particularly in automotive applications [17]. Bending test results are given in Figure 5.…”
Section: Tensile and Bending Testsmentioning
confidence: 99%